Prevalence and factors associated with positive Pap rural populations of Peru. - Chávez, Susana (2015)
To determine the prevalence and factors associated abnormal in women in some rural and suburban communities in eight departments of Peru Pap. PROCEDURES: community-based study. Women between 18 and 67 years of 25 communities. An interview, gynecological examination and cervical cytology taking was performed using citobrush. The samples were read using the Bethesda System. Data were analyzed using SPSS 7.0. RESULTS: 725 women were included. The participants had an average of 36.8 years and a fertility rate of 5.3 children per woman. 13 (1.7%) women had cervical injury under and 12 (1.6%) lesion high grade. Two communities in the department of Ucayali and one in the department of La Libertad had the highest rates of high-grade lesion (7.0%). 11.4% and 4.0%. respectively. Women with high-grade lesion had no prior pelvic exam more frequently than women with normal Pap. Only the discovery of cervical friability was statistically associated (p <0.05) to the presence of intraepithelial lesion. CONCLUSION: There are areas in Peru with high prevalence of cervical injury, so it is necessary to promote the National Gynecologic Cancer Program and take steps to prevent mortality associated with this disease.